Cardiorespiratory Fitness Associates with Blood Pressure and Metabolic Health of Children-The Arkansas Active Kids Study - Diaz, Eva C; Weber, Judith L; Adams, Sean H; Young, Catarina G; Bai, Shasha; Børsheim, Elisabet (Medicine and science in sports and exercise, 2021)
High blood pressure (HBP) in children causes preclinical damage to the heart and accelerates atherosclerosis. Current pharmacological treatments have limited ability to prevent end-organ damage, particularly that of the kidneys. A contrasting element between adult versus pediatric HPB treatment is the emphasis in adults on exercise regimens that target increments in cardiorespiratory fitness (CRF; peak oxygen consumption [V˙O2peak]). The aim of this study was to evaluate the association of CRF with blood pressure percentiles and blood pressure status in children with normal and excessive adiposity (NA vs EA). An exploratory aim was to measure associations of CRF with (a) other cardiovascular disease risk factors commonly found in children with HBP and (b) kidney function.INTRODUCTIONHigh blood pressure (HBP) in children causes preclinical damage to the heart and accelerates atherosclerosis. Current pharmacological treatments have limited ability to prevent end-organ damage, particularly that of the kidneys. A contrasting element between adult versus pediatric HPB treatment is the emphasis in adults on exercise regimens that target increments in cardiorespiratory fitness (CRF; peak oxygen consumption [V˙O2peak]). The aim of this study was to evaluate the association of CRF with blood pressure percentiles and blood pressure status in children with normal and excessive adiposity (NA vs EA). An exploratory aim was to measure associations of CRF with (a) other cardiovascular disease risk factors commonly found in children with HBP and (b) kidney function.Children (n = 211) attended one study visit. CRF was measured using an incremental bike test and body composition by dual-energy x-ray absorptiometry. Fat-free mass (FFM) index was calculated as kilograms of FFM per square meter. Multiple logistic and linear regression analyses were used to model the probability of HBP and other variables of interest (plasma lipids, HOMA2-IR, alanine aminotransferase, and estimated glomerular filtration rate) against V˙O2peak.METHODSChildren (n = 211) attended one study visit. CRF was measured using an incremental bike test and body composition by dual-energy x-ray absorptiometry. Fat-free mass (FFM) index was calculated as kilograms of FFM per square meter. Multiple logistic and linear regression analyses were used to model the probability of HBP and other variables of interest (plasma lipids, HOMA2-IR, alanine aminotransferase, and estimated glomerular filtration rate) against V˙O2peak.CRF interacted with adiposity status in predicting the probability of HBP. Each additional milliliter per minute per FFM index in V˙O2peak decreased the odds of HBP by 8% in the EA group only (odds ratio = 0.92, 95% confidence interval = 0.87-0.99). Systolic and diastolic blood pressure percentiles decreased, and estimated glomerular filtration rate increased with increasing CRF in both adiposity-level groups. HOMA2-IR and alanine aminotransferase decreased with increasing CRF in children with EA only.RESULTSCRF interacted with adiposity status in predicting the probability of HBP. Each additional milliliter per minute per FFM index in V˙O2peak decreased the odds of HBP by 8% in the EA group only (odds ratio = 0.92, 95% confidence interval = 0.87-0.99). Systolic and diastolic blood pressure percentiles decreased, and estimated glomerular filtration rate increased with increasing CRF in both adiposity-level groups. HOMA2-IR and alanine aminotransferase decreased with increasing CRF in children with EA only.Higher CRF associated with decreased probability of clinical HBP, lower insulin resistance, and improved liver function in children with EA. Yet blood pressure percentiles and kidney function improved with increasing CRF irrespective of adiposity status.CONCLUSIONSHigher CRF associated with decreased probability of clinical HBP, lower insulin resistance, and improved liver function in children with EA. Yet blood pressure percentiles and kidney function improved with increasing CRF irrespective of adiposity status.